Factors affecting Muslim women's intention to wear hijab : a study from Malaysian perspective - Sharifah Hadijah binti Syed Hussin (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2019)
The main focus of the research is to know the factors that affect Muslim women's intention to wear a Hijab in Malaysia by using the Theory of Planned Behaviors (TPB). Hijab is considered as an Islamic culture that requires all Muslim women to wear it. The growth of awareness among women to wear the Hijab has driven the production of Hijab by marketers because of the increasing demand in Malaysia. Yet it become of the Muslimah fashion attire nowadays. In order to identify the factors that affect Muslim women's intention to wear a Hijab, data were collected from 300 respondents randomly which comprise Muslim women from both West and East Malaysia. TPB was used as the conceptual framework and the relationship variables identified are attitude, subjective norms, perceived behavioral control, religiosity and culture. The data collected were tested using multiple regression analysis in SPSS. The findings show that all the variables are significant and can be accepted and supported. It shows that culture was the main factor influencing Muslim women to wear a Hijab. The result also showed that the theoretical framework used in this study is successful in achieving the research objectives. Besides, the research is also useful for practitioners and marketing managers especially those involved in the Hijab industry. Researchers and academicians also will reap the benefit through the findings highlighted and can understand better the intention of Muslim women in wearing a Hijab and its implication in Islamic practices.